PERLINDUNGAN HUKUM TERHADAP BANK SEBAGAI KREDITUR BARU DALAM PENGALIHAN PIUTANG ATAS KREDIT PEMILIKAN RUMAH SECARA TOP UP - Justitia, Widya; Aidi, Zil (Jurnal Yuridis, 2017)
The purpose of this study is to determine and analyze the upcoming risks that can occur in the bank as a new creditor over the implementation of transfer of receivable house ownership credit (KPR) via top up. In addition, this study also discusses the form of ideal legal protection for banks as the new creditor over the transfer of house ownership credit via top up. The research that use Bank Tabungan Negara (BTN) Yogyakarta Branch as the respondent is a qualitative empirical legal research and analyze the data collected by qualitative descriptive method. Take over KPR via top up have a legal certainty risk associated with the interlude time between signing the agreement with the transfer of collateral from the old creditor to the new creditor. Currently, the legal protection for banks as the new creditor in the implementation of take over KPR via top up is only in the form of preventive protection that could be seen in precautionary actions to ensure the fullfillment of the rights and obligations of the parties. Furthermore, subrogation agreements are also required as a complement and legal basis to ensure the release of the collateral from the previous agreement.